Effects of Dietary Inclusion of Clostridium autoethanogenum Protein on the Growth Performance and Liver Health of Largemouth Bass (Micropterus salmoides) - Lu, Qisheng; Xi, Longwei; Liu, Yulong; Gong, Yulong; Su, Jingzhi; Han, Dong; Yang, Yunxia; Jin, Junyan; Liu, Haokun; Zhu, Xiaoming; Xie, Shouqi (Frontiers in Marine Science, 2021)
Clostridium autoethanogenum protein (CAP) is a novel protein source for aqua-feeds. The present study aimed to investigate the effects of dietary CAP on growth performance, immunity, and liver health status of juvenile largemouth bass (Micropterus salmoides). Four isonitrogenous and isolipid experimental diets were formulated to replace 0% (D1, control), 25% (D2), 50% (D3), and 75% (D4) of fish meal by CAP. Fish (15.05 ± 0.08g) were randomly fed one of four experimental diets for 8 weeks. The results showed that weight gain (WG), specific growth rate (SGR), feeding rate (FR), viscerosomatic index (VSI) and hepatosomatic index (HSI) of D4 group were significantly lower than D1, D2 and D3 groups (P < 0.05). With the increase of substitution level, the total antioxidant capacity (T-AOC) of liver tissue was significantly decreased, while the plasma alkaline phosphatase (AKP) activity was significantly increased (P < 0.05). Plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were significantly higher in D3 and D4 groups than D1 and D2 groups (P < 0.05). Replacing 50% or 75% fish meal by CAP significantly induced the transcription level of apoptosis-promoting genes (bad, bax), anti-apoptosis related genes (p53, bcl-2) and the apoptotic C. elegans death gene-3 like caspases (caspase-3, caspase-8, caspase-9, caspase-10) in liver, while suppressed the gene expression of the inflammatory factors (il-1β, il-8, tnf) in head kidney. At the same time, dietary inclusion of CAP elevated the protein expression of BCL-2, LC3A/B-I, and LC3A/B-II by inhibiting the phosphorylation of mTOR (P < 0.05). Moreover, the apoptosis rate of D3 and D4 groups were significantly increased (P < 0.05). Taken together, these results indicated that the optimal level of CAP replacing fish meal should be less than 50%, that has no negative effect on the growth performance and liver health of juvenile largemouth bass. In addition, excessive CAP inclusion may damage liver health by activating autophagy and apoptosis signaling pathways.